2008
DOI: 10.1007/978-1-4020-5555-3_11
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Cognitive Dissonance: State of the Science and Directions for Future Research

Abstract: The theory of cognitive dissonance is one of the most influential theories in social psychology. Since its initial publication 50 years ago, it has inspired more than 1,000 empirical papers. However, dissonance theory has not only had a profound impact on research in social psychology, it has also been used for designing interventions to address a variety of societal problems. In this short overview of the empirical literature on dissonance theory, we first introduce the definition of dissonance theory in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…There are some incentives such as Homophily, Cognitive dissonance, Echo chamber, Selective exposure, Information overload, Media bias, and Algorithmic bias, etc. are responsible for an ideologically polarized society In 1962 Festinger recommended cognitive dissonance theory but Fisher et al 2008 redefi ned cognitive dissonance as the "phenomenon by which people experience positive feelings when presented with information" ( Fischer et al 2008). The level of discrete media consumption activities is stimulated by this phenomenon, for example, the existence of the information that is underpinning perspective is likely to upsurge the probability of exposure, and as a result, the exposure to a different source of info is decreasing (Garrett 2009).…”
Section: That Initiates Polarizationmentioning
confidence: 99%
“…There are some incentives such as Homophily, Cognitive dissonance, Echo chamber, Selective exposure, Information overload, Media bias, and Algorithmic bias, etc. are responsible for an ideologically polarized society In 1962 Festinger recommended cognitive dissonance theory but Fisher et al 2008 redefi ned cognitive dissonance as the "phenomenon by which people experience positive feelings when presented with information" ( Fischer et al 2008). The level of discrete media consumption activities is stimulated by this phenomenon, for example, the existence of the information that is underpinning perspective is likely to upsurge the probability of exposure, and as a result, the exposure to a different source of info is decreasing (Garrett 2009).…”
Section: That Initiates Polarizationmentioning
confidence: 99%
“…Factors belonging to the former category can be seen as originating from the phenomenon of cognitive dissonance. Cognitive dissonance is an extensively studied phenomenon within the field of psychology, and refers to the discomfort experienced by people when presented by information that challenges their beliefs or decisions [22,23]. This discomfort in turn encourages certain behavior that causes polarization.…”
Section: Polarization Driversmentioning
confidence: 99%
“…According to CDT, discrepant cognitions arise when two or more elements of one's knowledge, belief, attitude, values, emotion, or behavior enter in conflict. 15 This situation triggers feelings of psychological discomfort-or dissonance-that individuals will be motivated to resolve to bring their thoughts into greater harmony. 16 Studies have shown that they will do so by altering the cognition that is the least resistant to changes.…”
Section: Research Approach and Theoretical Frameworkmentioning
confidence: 99%